Halal Business Practice: An Islamic Business Ethics Perspective - Ghozali, Mohammad; Yasin, Ahmad; Nasution, Saipul; Safitri, Aiza Rahma (AL-IKTISAB: Journal of Islamic Economic Law, 2024)
Islamic business ethics is a set of principles and norms that business people must uphold in transactions, behavior, and relationships to achieve business goals safely, these ethics aim as an effort by a business person so as not to get out of Islamic law. The culinary industry is rapidly growing in response to the increasing demand for halal food in scattered Muslim communities across Indonesia. This surge has created opportunities for entrepreneurs to establish halal restaurants, leading to intensified competition. It is crucial to adhere to Islamic teachings and ethical guidelines while running the business to ensure not only profits but also blessings, ensuring the business's longevity and success. This research provides information about halal business models and an overview of ethical information in doing business according to Islamic law in restaurant business practices. This research employs field research and a qualitative descriptive approach. For collecting the data, this study utilized observation, documentation, and direct interviews The results of this study show that halal business practices carried out in business activities follow the Islamic business principles, which can fulfill the characteristics of Islamic business by modelling the four characteristics of the Prophet Saw. as a reference for business practices carried out in all aspects of the business activities, including the characteristics of shiddiq, amanah, tabligh, and fathanah.